Christianity in Sub-Saharan Africa by Kenneth R. Ross, J. Kwabena Asamoah-Gyadu and Todd M. Johnson. - Bakare, Gideon (PentecoStudies, 2020)
ROSS, Kenneth R., J. Kwabena ASAMOAH-GYADU and Todd M. JOHNSON. Christianity in Sub-Saharan Africa. Edinburgh: Edinburgh University Press, 2017. 538pp. Hbk. ISBN: 9781474412032. £150.